Great Tradition And Its Legacy : the Evolution of Dramatic and Musical Theater in Austria and Central Europe. - Cherlin, Michael (Berghahn Books, 2004)
Both dramatic and musical theater are part of the tradition that has made Austria - especially Vienna - and the old Habsburg lands synonymous with high culture in Central Europe. Many works, often controversial originally but now considered as classics, are still performed regularly in Vienna, Prague, Budapest, or Krakow. This volume not only offers an excellent overview of the theatrical history of the region, it is also an innovative, cross-disciplinary attempt to analyse the inner workings and dynamics of theater through a discussion of the interplay between society, the audience, and perf.